2017
DOI: 10.1103/physrevd.95.034034
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian effective field theory study of the N*(1440) resonance in lattice QCD

Abstract: We examine the phase shifts and inelasticities associated with the N * (1440) Roper resonance and connect these infinite-volume observables to the finite-volume spectrum of lattice QCD using Hamiltonian effective field theory. We explore three hypotheses for the structure of the Roper resonance. All three hypotheses are able to describe the scattering data well. In the third hypothesis the Roper resonance couples the low-lying bare basis-state component associated with the ground state nucleon with the virtual… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 56 publications
4
47
0
1
Order By: Relevance
“…While we do not perform continuum and chiral extrapolations here, our data can be used for future such extrapolations. Chiral extrapolations of lattice scattering data using unitarized extensions of chiral effective theory [65,[67][68][69][70][71][72][73][74] have been performed, although to date cutoff effects have not been considered. Nonetheless, it is evident in our data that cutoff effects in both the scattering amplitude (shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we do not perform continuum and chiral extrapolations here, our data can be used for future such extrapolations. Chiral extrapolations of lattice scattering data using unitarized extensions of chiral effective theory [65,[67][68][69][70][71][72][73][74] have been performed, although to date cutoff effects have not been considered. Nonetheless, it is evident in our data that cutoff effects in both the scattering amplitude (shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In order to extrapolate to the physical point and continuum, a range of pion masses m π = 200 − 280 MeV and lattice spacings a = 0.050 − 0.086 fm are employed. Such extrapolations have been performed recently using chiral perturbation theory and its extensions [63][64][65][66][67][68][69][70][71][72][73][74] and treat all scattering data simultaneously. As these extrapolations are somewhat involved and have not yet treated cutoff effects, we present the determination of the amplitudes only in this work and leave extrapolation to the physical quark masses and continuum for the future.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that some authors interpret the Roper as a dynamically-generated baryon-meson resonance, without an explicit reference to three-quark systems, except for the nucleon and the Δð1232Þ [105][106][107][108]. As far as we know, there are no calculations of γ Ã N → Nð1440Þ transition form factors for intermediate and large Q 2 , based on dynamically-generated resonance models for the Roper.…”
Section: A Discussionmentioning
confidence: 99%
“…As far as we know, there are no calculations of γ Ã N → Nð1440Þ transition form factors for intermediate and large Q 2 , based on dynamically-generated resonance models for the Roper. Future lattice QCD simulations can help to understand the role of the baryon-meson contribution for the transition form factors at low Q 2 [107,108].…”
Section: A Discussionmentioning
confidence: 99%
“…The Graz-Ljubljana group has concluded that πN channel alone does not render a low-lying resonance and that coupling with ππN channels seems to be important, which supports the dynamical origin of the Roper. The Adelaide group analyzed two scenarios of the resonance formation in the framework of the Hamiltonian effective field theory [30,31], the dynamical generation and the generation through a lowlying bare-baryon resonant state: while both these effective models reproduce well the experimental phase shift by suitably adjusting model parameters, only the former scenario provides an adequate interpretation of the lattice results of the GrazLjubljana group [28]. The width of the Roper resonance and the quark mass dependence of its mass has also been investigated in relativistic baryon ChiPT [32,33].…”
Section: Introductionmentioning
confidence: 99%